The implementation of fuzzy logic in forecasting financial ratios - Tomasz Korol (Contemporary Economics, 2018)
This paper is devoted to the issue of forecasting financial ratios. The objective of the conducted research is to develop a predictive model with the use of an innovative methodology, i.e., fuzzy logic theory, and to evaluate its effectiveness. Fuzzy logic has been widely used in machinery, robotics and industrial engineering. This paper introduces the use of fuzzy logic for the financial analysis of enterprises. While many current phenomena in finance and economics are fuzzy, they are treated as if they are crisp. Fuzzy logic provides an appropriate tool for modeling imprecise, uncertain and ambiguous phenomena. Because the financial situation of a company is affected by many factors (economic, political, psychological, etc.) that cannot be precisely and unambiguously defined, the approach used in this paper greatly enhances the predictive power of financial analysis and makes it an economically useful tool for the management of enterprises. Empirically, this paper employs three testing samples: Central European enterprises, Latin American companies and global firms. From the verification of these models, it is evident that the refined processes are effective in improving the forecasting of financial situations of all three types of enterprises. The models created by the author are characterized by high efficiency. This study is one of the world's first attempts to combine ratio analysis with fuzzy logic to predict the financial situations of companies.
Keywords: G01; 330; decision support systems; financial ratios; fuzzy logic; forecasting; financial crisis